2022
DOI: 10.1021/acs.analchem.2c02388
|View full text |Cite
|
Sign up to set email alerts
|

Thionation toward High-Contrast ACQ-DIE Probes by Reprogramming the Aqueous Segregation Behavior: Enlightenment from a Sulfur-Substituted G-Quadruplex Ligand

Abstract: Small-molecule-based fluorescent chemosensors provide powerful tools for analytical chemistry. However, their organic essence often “cursed” them for aggregation-caused quenching (ACQ) in an aqueous context. Albeit the praxis of the disaggregation-induced emission (DIE) strategy as a potential solution, it still awaited improvement due to the uncontrollability of the aggregation/segregation process. To address this issue, herein, we supposed that sulfur substitution on a molecule could serve as a promising str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Notably, the LOD of SN-Cy5-S was 1.51 nM, which was lower than for the previously reported DIE probes (Table ). ,,, A Job’s plot experiment demonstrated that SN-Cy5-S and G4s combined in ratios of 1:1 or 2:1 (Figure S15), consistent with the results of the above-described nonlinear fitting.…”
Section: Resultssupporting
confidence: 84%
“…Notably, the LOD of SN-Cy5-S was 1.51 nM, which was lower than for the previously reported DIE probes (Table ). ,,, A Job’s plot experiment demonstrated that SN-Cy5-S and G4s combined in ratios of 1:1 or 2:1 (Figure S15), consistent with the results of the above-described nonlinear fitting.…”
Section: Resultssupporting
confidence: 84%
“…The development of luminescent materials coupled with the rapid evolution of optical microscopy techniques has allowed generation of valuable knowledge in the roles and functions that G4s play in cells. ,, However, in many conventional systems, fluorophores experience the phenomenon of aggregation-induced quenching (ACQ) that limits their full potential as diagnostic agents . Recently, we and others have introduced a selective G4 recognition strategy that relies on the disassembly of self-aggregated dyes, namely, disaggregation-induced emission (DIE). Dyes operating through DIE display remarkable topological/sequence selectivity , for G4s and have broad applicability in cellular systems. ,, …”
mentioning
confidence: 99%
“…Recently, we and others have introduced a selective G4 recognition strategy that relies on the disassembly of self-aggregated dyes, namely, disaggregation-induced emission (DIE). Dyes operating through DIE display remarkable topological/sequence selectivity , for G4s and have broad applicability in cellular systems. ,, …”
mentioning
confidence: 99%